Maternal basking behaviour determines offspring sex in a viviparous reptile. - Wapstra, Erik (2004)
Two primary dichotomies within vertebrate life histories involve reproductive mode (oviparity versus viviparity) and sex determination (genotypic sex determination versus environmental sex determination). Although reptiles show multiple evolutionary transitions in both parameters, the co-occurrence of viviparity and environmental-dependent sex determination have heretofore been regarded as incompatible. Our studies on the viviparous lizard Niveoscincus ocellatus show that the extent of basking by a female influences the sex of her offspring. Critically, our data reveal this effect both in the field (via correlations between date of birth and litter sex ratio) and in a laboratory experiment (females with reduced basking opportunities produced more male offspring). Changes in thermoregulatory behaviour thus allow pregnant female lizards to modify the sex of their offspring.